Feeding habits and novel prey of larval fishes in the northern San Francisco Estuary. Issue 6 (23rd September 2021) - Jungbluth, Michelle J.; Burns, Jillian; Grimaldo, Lenny; Slaughter, Anne; Katla, Aspen; Kimmerer, Wim
Abstract: Food limitation can dampen the survival and growth of fish species during early development. To investigate prey diversity important to the planktivorous larval longfin smelt ( Spirinchus thaleichthys ) and Pacific herring ( Clupea pallasii ) from the San Francisco Estuary, we used DNA metabarcoding analysis of the cytochrome oxidase I gene on the guts of these fishes and on environmental zooplankton samples, in comparison with results from abundance analyses of zooplankton samples. Overall, both fish consumed the prey that were commonly available and relatively abundant: Diets were dominated by arthropods but also included soft‐bodied and difficult to identify organisms. Prey taxa substantially overlapped between the two species (Schoener's index = 0.66), and alpha diversity analysis suggested high variability in the content of guts from different individuals. Abundant prey taxa in both fish species included the copepods  Eurytemora carolleeae, Acanthocyclops americanus, and A .  robustus ; Acanthocyclops  spp. are difficult to distinguish morphologically. Differential abundance analysis suggested that both species consumed the most abundant zooplankton in lower proportions than their availability in the environment. A few uncommon prey observed in the diets may hint at feeding strategies employed by the larvae, such as herring DNA in the longfin smelt diets, suggesting feeding on eggs near substrates or schooling behavior. Herring consumed the small (<0.5 mm) copepod Limnoithona tetraspina  much more frequently (30%) than did smelt (2%), possibly indicating differences in foraging behavior or sensory abilities. Among the unexpected prey found in the diets was the cnidarian  Hydra oligactis, the polychaete  Dasybranchus  sp., and the copepod  Mesocyclops pehpeiensis, a species not previously described in the San Francisco Estuary. Our findings illustrate the power of molecular methods in revealing feeding patterns and novel plankton diversity that can be undetectable with complementary morphological analysis methods. Abstract : We used dietary DNA metabarcoding analysis of the mitochondrial cytochrome oxidase I gene to study the diets of larval fishes in the San Francisco Estuary and found a high level of overlap between the two species primarily dominated by calanoid and cyclopoid copepods. We also found previously unidentified prey items in the diets of both fishes, diet items that may be indicative of feeding in a particular part of their habitat or of schooling behavior, and species‐level identification of previously poorly described zooplankton in the estuary.